2011
DOI: 10.1177/0013124511408715
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Associations Among Home–School Dissonance, Amotivation, and Classroom Disruptive Behavior for Urban High School Students

Abstract: The current study examined the association among home–school dissonance, amotivation, and classroom disruptive behavior among 309 high school juniors and seniors at two urban high schools in the Southern region of the country. Students completed two subscales of the Patterns of Learning Activities Scales (PALS) and one subscale of the Academic Motivation Scale (AMS). ANCOVA analyses revealed significant differences in classroom disruptive behaviors for the gender independent variable. Controlling for gender in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…Another principle of the ecological model is that developmental processes occurring in various environments are mutually dependent. This suggests that problem behavior in one environment can transfer to another, for example, from home to school and vice versa (Bronfenbrenner, 1986;Brown-Wright et al, 2013;DiLalla & Mullineaux, 2008;Sameroff, 2000). A way in which a child's behavior in an educational setting can be affected by poor family functioning is through coercive interactions.…”
mentioning
confidence: 99%
“…Another principle of the ecological model is that developmental processes occurring in various environments are mutually dependent. This suggests that problem behavior in one environment can transfer to another, for example, from home to school and vice versa (Bronfenbrenner, 1986;Brown-Wright et al, 2013;DiLalla & Mullineaux, 2008;Sameroff, 2000). A way in which a child's behavior in an educational setting can be affected by poor family functioning is through coercive interactions.…”
mentioning
confidence: 99%
“…As Sharma (2014) succinctly elucidates, when incongruity exists between ideas and actions, something must change so that the dissonance is dispelled. Festinger (1957), Harmon-Jones et al (2011) andBrown-Wright et al (2013) have all defined dissonance as a mentally distressing situation from which individuals are compelled to extricate themselves by modifying belief systems and behaviour patterns. Hasan and Nasreen (2012) see dissonance as the factor prompting individuals to bestow concord and consistency upon discordant elements to thereby eliminate psychological distress.…”
Section: Post Purchase Dissonancementioning
confidence: 99%
“…Notably, researchers to-date who have studied HSD using quantitative methods have largely relied on a single scale (Arunkumar et al, 1999;Brown-Wright, Tyler, Graves, Thomas, Stevens-Watkins, & Mulder et al, 2013;…”
Section: The Current Studymentioning
confidence: 99%
“…Studies of African American high school students have found positive associations between HSD and amotivation, cheating, disruptive behavior, and performance avoidance, and a negative association with grades (Brown-Wright et al, 2013;Tyler et al, 2010).…”
Section: Operationalizing Hsd In a Surveymentioning
confidence: 99%
See 1 more Smart Citation